Comparative Study Between Dutasteride Monotherapy Versus Combination of Dutasteride and Tamsulosin in Management of BPH (Bangladesh Journal of Urology, 2026)
Objectives: To evaluate whether combination therapy with Dutasteride and Tamsulosin is more effective than Dutasteride monotherapy for improving symptom of BPH.Patient and method: This hospital based, prospective, randomized, comparative study will be conducted in Urology Dept. BSMMU from January 2011 to June 2012.Total 160 cases were selected according to inclusion and exclusion criteria. 80 case for combination therapy and 80 cases for monotherapy. Men 50-75 years with clinical diagnosis of prostatic hyperplasia, international prostate symptom score points 8 to 35, prostate volume 30 to 50 cc, total serum prostate specific antigen 1.5 to